The Metacognitive Awareness Levels of Religious Education Teachers - Baltacı, Ali (My University, 2019)
The purpose of this research is to analyze religious education teachers’metacognitive awareness and to find out whether a significant differenceexists according to gender, education level, professional tenure, and age.The sample group of this research which designed by correlational surveymodel is the 471 religious education teachers working in Ankara. For thesample group, the Metacognitive Awareness Inventory developed bySchraw and Dennison (1994) was applied. According to the results of theresearch, teachers were found to have moderate cognitive awareness.While educational level, professional tenure and age variables werechanging significantly with metacognitive awareness, gender was not. Also,whereas education status, professional tenure, and age were found to havean important effect on metacognitive awareness levels, gender does nothave such an effect. This study is important in that the Turkish educationalsciences studying the concept of metacognition on the sample of religiouseducation teachers and it is a pioneering work in the literature. It is hopedthat the results obtained in the research will contribute to the efforts of morequalified teachers by establishing the levels of cognitive awareness ofreligious education teachers and to provide guidance for future research.

Bu araştırmada, din öğretimi öğretmenlerinin üst-bilişsel farkındalıkdurumlarını incelenmesi ve farkındalık düzeylerinin cinsiyet, eğitim durumu,mesleki kıdem ve yaş bakımından karşılaştırılması amaçlanmıştır. İlişkiseltarama modelinde tasarlanan bu araştırmanın örneklem grubu, Ankara ilindeçalışmakta olan 471 din öğretimi öğretmenidir. Örneklem grubuna, Schrawand Dennison (1994) tarafından geliştirilen Üst-bilişsel Farkındalık Envanteriuygulanmıştır. Araştırma sonuçlarına göre, öğretmenlerin orta düzeyde üstbilişsel farkındalığa sahip oldukları belirlenmiştir. Eğitim durumu, meslekikıdem ve yaş değişkenleri üst-bilişsel farkındalık ile anlamlı bir şekildedeğişmekteyken, cinsiyet değişkeni üst-bilişsel farkındalığıyordamamaktadır. Ayrıca eğitim durumu, mesleki kıdem ve yaş üst-bilişfarkındalık düzeyleri üzerinde etkili iken; cinsiyetin böylesi bir etkisibulunmamaktadır. Bu çalışma din öğretimi öğretmeni örneklemi üzerindeüst-biliş kavramını inceleyen Türk din eğitimi bilimleri alanyazınındaki öncüçalışma olması bakımından önem taşımaktadır. Araştırmada elde edilensonuçların, din öğretimi öğretmenlerinin üst-bilişsel farkındalık düzeylerinintespit edilmesi ile daha nitelikli öğretmen yetiştirme çabalarına katkısağlaması ve ileride yapılacak araştırmalar için yol gösterici olması ümitedilmektedir.
Din Öğretimi Öğretmenlerinin Üst-Bilişsel Farkındalık Düzeyleri
Keywords: Eğitim, Eğitim Araştırmaları; Eğitim, Özel; Psikoloji; Tarih